Generation of vector beams with different polarization singularities based on metasurfaces. (1st April 2022) - Liu, Danhua; Zhou, Changda; Lu, Peiyao; Xu, Jilian; Yue, Zhiyuan; Teng, Shuyun
Abstract: In view of wide applications of vector beams and powerful light manipulation ability of metasurfaces, this paper studies the generation of two kinds of vector beams with different polarization singularities based on metasurfaces. One kind of vector beams are the linearly polarized vector beam with uncertain polarization orientation and the other kind of vector beams are the elliptically polarized vector beam with hybrid polarization states with uncertain polarization orientation, ellipticity and handedness. These vector beams can be decomposed into two or more uniform polarization states carrying the spiral phases. The metasurfaces consisting of rotated cross nanoholes are designed to generate vector beams on basis of the decomposition of vector beams and phase modulation of nanoholes. The simulation results verify the availability of the designed metasurfaces and the experiment results validate the generation of two kinds of vector beams. The generation of complex vector beams based on compact metasurfaces can bring more application possibilities of vector beams in classical physics and quantum sciences.